Agent‐based models of inflammation in translational systems biology: A decade later. (1st July 2019) - Vodovotz, Yoram; An, Gary
Abstract: Agent‐based modeling is a rule‐based, discrete‐event, and spatially explicit computational modeling method that employs computational objects that instantiate the rules and interactions among the individual components ("agents") of system. Agent‐based modeling is well suited to translating into a computational model the knowledge generated from basic science research, particularly with respect to translating across scales the mechanisms of cellular behavior into aggregated cell population dynamics manifesting at the tissue and organ level. This capacity has made agent‐based modeling an integral method in translational systems biology (TSB), an approach that uses multiscale dynamic computational modeling to explicitly represent disease processes in a clinically relevant fashion. The initial work in the early 2000s using agent‐based models (ABMs) in TSB focused on examining acute inflammation and its intersection with wound healing; the decade since has seen vast growth in both the application of agent‐based modeling to a wide array of disease processes as well as methodological advancements in the use and analysis of ABM. This report presents an update on an earlier review of ABMs in TSB and presents examples of exciting progress in the modeling of various organs and diseases that involve inflammation. This review also describes developments that integrate the use of ABMs with cutting‐edge technologies such as high‐performance computing, machine learning, and artificial intelligence, with a view toward the future integration of these methodologies. This article is categorized under: Translational, Genomic, and Systems Medicine > Translational Medicine Models of Systems Properties and Processes > Mechanistic Models Models of Systems Properties and Processes > Organ, Tissue, and Physiological Models Models of Systems Properties and Processes > Organismal Models Abstract : Agent‐based models (ABMs) of inflammation: past, present, and future. Initial (First‐Gen) ABMs of inflammation served as means for hypothesis instantiation, dynamic knowledge representation, and as proof‐of‐concept tools for core translational systems biology applications such as in silico clinical trials and patient‐specific models. Due to methodological and conceptual advances, next‐generation (Next‐Gen) agent‐based modeling of inflammation with a higher degree of fidelity to their reference systems (i.e., greater detail in number and types of components, and disease phenotypes represented) is poised to advance further in the coming decade.